NILAI MORAL DALAM LAGU ANAK TEMPO DULU - Suprihatien Suprihatien; Rini Damayanti (Jurnal Inovasi Penelitian, 2020)
Children’s songs used to be able to instill moral values, character, and knowledge. Through songs children learn various things. The purpose of this study is to describe the moral values contained in old children’s song lyrics. This research uses descriptive qualitative type. The object of research aspects of moral education. This aspect was analysed from the text of children’s songs the past. Children’s songs used to have good moral values. The moral values are morality of God, moral of philosophical ideology, moral of moral ethics, and moral of discipline.